Teaching Trigonometry Based on Realistic Mathematics Education and Game-Based Learning Approach - Nguyen Tien Da; Do Diep Anh; Pham Thi Chau Giang; Phung Phuong Dung; Dang Bui Khanh Linh (Pendidikan Matematika STKIP Kusuma Negara, 2024)
Trigonometry, often perceived as abstract and challenging, can hinder its potential to equip students with crucial mathematical skills. We propose a novel approach—